TEACHING LEADERSHIP AND ADMINISTRATION AT A FACULTY OF THEOLOGY: PRACTICAL-THEOLOGICAL REFLECTIONS - Nell, Ian 1961- (2014)
The on-going processes of decline taking place in mainline churches all over the world in combination with developments in the direction of pluralism, consumerism and globalization pose many challenges to the teaching of leadership and administration at Faculties of Theology. Not only do we find much "crisis lan-guage" and even some unease with the use of leadership terminology in theological discourses, but we also see challenges to deeply-held convictions on the traditional understanding of the offices and ministry of the church. The values and underlying assumptions about these notions are contested areas in scholarly research. At the same time we see the development of alternative forms of leadership as well as the rapid growth of African Independent Churches within the African context. The article probes different aspects of leadership and administration and attempts to clarify some points of departure for the on-going conversation. Part of the argument is that the teaching of leadership and administration, in preparing students for their role in Christian faith communities, rests upon four different pedagogies. These pedagogies each contribute towards an integrated spirituality as a prerequisite for authentic leadership. In conclusion, some practical suggestions are proposed as pointers for the future for teaching this challenging field at Faculties of Theology.
Keywords: Administration; Faith Formation; Leadership; Pedagogy; Theological Education